Large-scale-integration and collective oscillations of 2D artificial cells - Joshua Ricouvier; Pavel Mostov; Omer Shabtai; Ohad Vonshak; Alexandra Tayar; Eyal Karzbrun; Aset Khakimzhan; Vincent Noireaux; Shirley Shulman Daube; Roy Bar-Ziv (Nature Communications)
Abstract The on-chip large-scale-integration of genetically programmed artificial cells capable of exhibiting collective expression patterns is important for fundamental research and biotechnology. Here, we report a 3D biochip with a 2D layout of 1024 DNA compartments as artificial cells on a 5 × 5 mm2 area. Homeostatic cell-free protein synthesis reactions driven by genetic circuits occur inside the compartments. We create a reaction-diffusion system with a 30 × 30 square lattice of artificial cells interconnected by thin capillaries for diffusion of products. We program the connected lattice with a synthetic genetic oscillator and observe collective oscillations. The microscopic dimensions of the unit cell and capillaries set the effective diffusion and coupling strength in the lattice, which in turn affects the macroscopic synchronization dynamics. Strongly coupled oscillators exhibit fast and continuous 2D fronts emanating from the boundaries, which generate smooth and large-scale correlated spatial variations of the oscillator phases. This opens a class of 2D genetically programmed nonequilibrium synthetic multicellular systems, where chemical energy dissipated in protein synthesis leads to large-scale spatiotemporal patterns.